2022
DOI: 10.1111/ggi.14526
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effectiveness of online interactive courses on loneliness and quality of life of older adults in the community during the COVID‐19 pandemic: A pilot study and a randomized controlled trial

Abstract: Background The early stage of the COVID‐19 pandemic was a critical time for increasing loneliness, especially for older people. However, there is insufficient existing research on associated interventions and their effectiveness. Aim This study aimed to investigate the effectiveness of an 8‐week online interactive course on the loneliness, depression, social support, and quality of life (QOL) of older adults in the community during the COVID‐19 pandemic. Methods A single‐blind randomized controlled trial was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Therefore, it can potentially be improved through some interventions to increase social interaction. For example, a pilot study of a randomized controlled trial showed that an eight-week online interactive course using LINE reduced loneliness and improved the psychological health and social relationship domains of QOL among elderly individuals during the COVID-19 pandemic [ 9 ]. Further, a community-based interventional longitudinal study found that more frequent participation in eight-week social interaction sessions improved the QOL of elderly individuals when compared with less frequent participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can potentially be improved through some interventions to increase social interaction. For example, a pilot study of a randomized controlled trial showed that an eight-week online interactive course using LINE reduced loneliness and improved the psychological health and social relationship domains of QOL among elderly individuals during the COVID-19 pandemic [ 9 ]. Further, a community-based interventional longitudinal study found that more frequent participation in eight-week social interaction sessions improved the QOL of elderly individuals when compared with less frequent participation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, poor HRQOL was found to be a predictor of hospitalization and mortality among patients undergoing hemodialysis [ 7 ], while a separate study showed that having more social ties was associated with greater resistance to upper respiratory tract infections [ 8 ]. In addition, the results of a pilot randomized controlled trial conducted during the coronavirus disease 2019 (COVID-19) pandemic demonstrated that in older adults an eight-week online interactive course using LINE (a freeware app for instant communications with exchanging texts, images, videos, and audios on electronic devices) reduced loneliness, as well as improved scores on the HRQOL domains of psychological health and social relationships [ 9 ]. Together, these findings suggest that the social aspect of HRQOL is modifiable and that it may be a risk factor for CAP.…”
Section: Introductionmentioning
confidence: 99%
“…In most fields of medicine, isolation measures during the COVID-19 pandemic led to further development of online care provision [ 17 - 19 ]. Digital treatment strategies hold great promise for individuals with PCS, who often experience impaired mobility, as these strategies facilitate therapy access and adherence [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Especially during the COVID pandemic, the risks faced by older adults (particularly those in long-term care institutions) significantly increased, exacerbating their sense of isolation and leading to sleep disruptions, thereby aggravating sleep issues. [15][16][17][18][19][20] Transitioning to long-term care institutions often brings about challenges for older individuals, including the loss of familiar social networks and life goals, 21,22 difficulties in forming new relationships, 23 and apprehension about the quality of care. 24 These factors render them susceptible to anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…However, sleep quality problems in older people in long‐term care institutions were usually underestimated or overlooked 7 . Especially during the COVID pandemic, the risks faced by older adults (particularly those in long‐term care institutions) significantly increased, exacerbating their sense of isolation and leading to sleep disruptions, thereby aggravating sleep issues 15–20 …”
Section: Introductionmentioning
confidence: 99%